Keanekaragaman dan Status Konservasi Ikan Yang Tertangkap Pada Alat Tangkap Gillnet Tetap Di PPN Sungailiat - Feniola, Livia; Pratiwi, Fika Dewi; Muftiadi, Muhammad Rizza (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2024)
Open access to marine resources causes people to fish without control and ignore conservation and trade status. Theseactivities can cause population decline and population can lead to overfishing.. This is due to the lack of availability ofinformation and scientific data to fishermen regarding the conservation status of fish species. Therefore, this study aimsto identify and determine the conservation status of fish species caught using fixed gillnet fishing gear in PPN Sungailiat.Data collection was carried out in March-May 2024 at the PPN Sungailiat, Bangka Regency. This study uses survey andobservation methods with qualitative descriptive data analysis. The results showed that there were 13 families identified.The main catch in this study contained 12 species and by-catch there were 7 species. The conservation status of fishspecies caught on gillnet fishing gear remains at the Sungailiat VAT according to national regulations based on the Decreeof the Minister of Marine Affairs and Fisheries No. 01 of 2021 with unprotected status. Meanwhile, the conservationstatus of fish species based on IUCN has 6 categories, including 3 species of fish classified as Not Evaluated (NE), 5species classified as Least Concern (LC), 2 species classified as Near Threatened (NT), 2 species classified as Vulnerable(VU), 5 species classified as Endangered (EN) and 2 other species classified as Critically Endangered (CR). Meanwhile,the trade status based on CITES has 2 species of fish classified in Appendix II, namely Rhynchobatus australiae (palmray) and Rhina ancylostomus (barong shark). Based on the results of conservation and trade status, several managementapproaches need to be taken towards fisheries resources so that their populations are maintained.